Lights, Policy, Action: A Multi-Level Perspective on Policy Instrument Mix Interactions for Community Energy Initiatives - Aamina Teladia; Henny van der Windt (Energies)
Community energy initiatives (CEIs) have the potential to accelerate energy transitions, but their scalability depends heavily on the alignment of policies across various governance levels. This study offers a comprehensive analysis of the multi-level policy instrument mix (PIM) supporting CEIs in the Netherlands, using the Multi-Level Perspective (MLP) to conceptualize CEIs as niche innovations within the broader energy regime. Our findings reveal that while national, regional, and local policies in the Netherlands align with overarching decarbonization and community involvement goals, significant misalignments persist. Specifically, the 50 percent local ownership ambition is inconsistently enforced, and grid infrastructure bottlenecks continue to hinder project implementation. These gaps underscore the need for improved coordination and clear role definitions across governance levels. In contrast, well-aligned policy instruments (such as coherent subsidy schemes and regional plans under the national Climate Act) have played a tangible role in supporting the growth of CEIs. This multi-level analysis contributes valuable insights not only for the Netherlands but also for countries seeking to integrate CEIs into their energy strategies. We conclude that a cohesive policy framework—combining top-down targets, bottom-up empowerment, and cross-level collaboration—is essential to empower communities and accelerate a just energy transition.